Building a White Nation Propaganda, Photography, and the Apartheid Regime Between the Late 1940s and the Mid-1970s - Jörder, Katharina (Leuven University Press, 2023)
A unique study of South African propaganda photography during apartheid. Throughout the apartheid era, South Africa maintained a wide-reaching propaganda apparatus. At its core was the information service that strongly capitalised on photography to visually articulate the minority regime's racist political messages, promote Afrikaner nationalism, and consolidate White rule. By unearthing a substantial corpus of photographs that so far have been hidden in archives, this book offers a distinctive perspective on the institutional context of the regime's photographic production and how it was tightly linked to the objective to build a White nation. Through scrutiny of the photographic material's iconographies, its circulation in printed matters, and a comparison with works by photographers like Margaret Bourke-White, Ernest Cole, and David Goldblatt, readers gain fresh insight into the country's visual culture of the period. Based on the ambiguity of photographs, the monograph challenges the alleged dichotomy between so-called pro- and anti-apartheid photographies, highlighting how the regime was able to position photographs in the grey area of inconspicuousness. By blending photo theory and art historical analysis with historical studies, Building a White Nation will appeal to scholars and postgraduate students in cultural studies interested in photo history and theory, visual culture and art history, African studies, South African photography, Afrikaner nationalism, propaganda studies, postcolonial studies, and archive theory. Ebook available in Open Access. This publication is GPRC-labeled (Guaranteed Peer-Reviewed Content).